2017
DOI: 10.1155/2017/1294193
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Evaluation of Mobile Applications for Instant Messaging on iOS Devices

Abstract: Nowadays, instant messaging applications (apps) are one of the most popular applications for mobile devices with millions of active users. However, mobile devices present hardware and software characteristics and limitations compared with personal computers. Hence, to address the usability issues of mobile apps, a specific methodology must be conducted. This paper shows the findings from a systematic analysis of these applications on iOS mobile platform that was conducted to identify some usability issues in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
(66 reference statements)
1
15
0
Order By: Relevance
“…A similar finding was reported in another app review study (Caro-Alvaro et al, 2017). Furthermore, although 3.3 is a good average, this rating may not correlate with effectiveness and quality; rather, it may be a reflection of usability.…”
Section: Main Findingssupporting
confidence: 86%
“…A similar finding was reported in another app review study (Caro-Alvaro et al, 2017). Furthermore, although 3.3 is a good average, this rating may not correlate with effectiveness and quality; rather, it may be a reflection of usability.…”
Section: Main Findingssupporting
confidence: 86%
“…Particularly for apps from the Apple store, this resulted in the exclusion of a large number of apps. Another mobile app review found more than half of the iOS apps tested in their study had no rating [37]. This may limit the range of apps that smokers using iOS are likely to download, but it is unlikely to have impacted the conclusions of our review, as our interest was in popular apps.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, the methodical evaluation [39] carried out here to detect usability issues was previously tested successfully on two types of apps: diabetes management apps [ 42,43] and spreadsheet apps [41]. Additionally, these authors applied this methodical evaluation on previous studies in IM environments [64,65]. e results of these studies (as well as this study about IM apps) show that it is necessary to apply both KLM and heuristic evaluation methods in order to detect more usability problems than when only one of them is used.…”
Section: Discussionmentioning
confidence: 99%